'DO I HAVE TO CHOOSE?' TWO CHILDREN VS FOUR CHILDREN IN BALI’S FAMILY PLANNING PROGRAM - Anastasia Septya Titisari; Carol Warren; Anja Reid; Luh Kadek Ratih Swandewi (Universitas Airlangga, 2022)
The Indonesian family planning program has been running for over five decades. Until the present, the implementation of this program still generates debate over important policy issues. On June 14th, 2019, the Balinese provincial government released a new pro-natalist family planning policy No.1545 (Keluarga Berencana Krama Bali) to respond to the concerns from the national family planning program two-child policy success. What are the implications for Balinese women's position in response to the political and cultural policies that impact their reproductive rights? This study analyzes the tensions between the national family planning program's two-child policy and the recent local Balinese Keluarga Berencana Krama model by focusing on Balinese women's perspectives. Ethnographic research was conducted from January to February 2020 in Bali. This study indicates that the women's fertility decisions were constrained by patrilineal structures, economic stresses, and government population policies. Krama Bali, which encourages a four children model according to the Balinese naming system, complicates the triple burden impacts on Balinese women's agency. The new pro-natalist provincial policy explicitly prioritizes cultural values and indirectly exacerbates the pressure to produce inheriting sons. Balinese women had to choose between cultural preservation and economic considerations, which intensified the tensions between their productive, reproductive, and customary (adat) obligations. Internal and external pressures imposed upon the Balinese women participants have forced them to navigate conflicting economic, political, and cultural demands with varying degrees of agency.